Managerial nursing competencies in the expansion of the Family Health Strategy - Ingrid Margareth Voth Lowen; Aida Maris Peres; Karla Crozeta; Elizabeth Bernardino; Carmem Lúcia Colomé Beck (SciELO, 2015)
Abstract OBJECTIVE To relate the managerial competencies required of nurses with the process of change experienced in the expansion of the Family Health Strategy (FHS). METHOD A qualitative research conducted in primary health care in a southern Brazilian city, through interviews with 32 managerial and clinical nurses. The interviews were processed by IRAMUTEQ software. The resulting classes were examined under five managerial competencies to promote change. RESULTS The four classes obtained from data were: the Family Health Strategy expansion process; confrontations and potentialities; mobilization for the change; innovations in medical and nursing consultations. The classes were related to one or more competencies. CONCLUSION The expansion of the Family Health Strategy requires managerial competencies of implementing and sustaining change, negotiating agreements and commitments, using power and influence ethically and effectively, sponsoring and selling new ideas, and encouraging and promoting innovation.